2011
DOI: 10.1177/039463201102400228
|View full text |Cite
|
Sign up to set email alerts
|

Ulerythema Ophryogenes, a Rare and Often Misdiagnosed Syndrome: Analysis of an Idiopathic Case

Abstract: Keratosis pilaris (KP) is a follicular hyperkeratosis disorder which is frequently detected in the adult population (44%), mostly in female adolescents (80%). It is a genetic autodominant dermatosis with variable penetrance, but no specific gene association has been determined, even though association to the presence of chromosome 18p deletion has been reported in some cases. We report the case of a 51-year-old Caucasian woman affected by keratosis pilaris gradually progressing with age and with a story of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Considerable attention has recently been devoted to the study ofcytokines, and in particular IL-l family mechanisms having the ability to induce biological activities on mast cells. One of the hypotheses is that IL-18 activates several cells through its receptor, including monocytes, lymphocytes basophils and mast cells (41,(58)(59)(60)(61)(62). Since IL-I stimulates PGE2 in macrophages, we hypothesize that IL-18 stimulates arachidonic acid in human mast cells and then may affect the production of prostaglandins such as PG0 2.…”
Section: Discussionmentioning
confidence: 96%
“…Considerable attention has recently been devoted to the study ofcytokines, and in particular IL-l family mechanisms having the ability to induce biological activities on mast cells. One of the hypotheses is that IL-18 activates several cells through its receptor, including monocytes, lymphocytes basophils and mast cells (41,(58)(59)(60)(61)(62). Since IL-I stimulates PGE2 in macrophages, we hypothesize that IL-18 stimulates arachidonic acid in human mast cells and then may affect the production of prostaglandins such as PG0 2.…”
Section: Discussionmentioning
confidence: 96%
“…Many authors reported that cytokine imbalances in autism have pathological roles and have important interaction with the nervous system, contributing to the dysfunction in autism spectrum disorders (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Several authors have reported that elevated cytokines in the cerebral spinal fluid of living autistic children play an important role in the neuroinflammatory process linked to this disease(s). Many authors reported that cytokine imbalances in autism have pathological roles and have important interaction with the nervous system, contributing to the dysfunction in autism spectrum disorders (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%